Peningkatan Literasi Karya Tulis Ilmiah pada Mahasiswa Pendidikan Jarak Jauh - Rahmat, Hayatul Khairul; Wahyuningtyas, Ayu; Qodariah, Qodariah; Ali, Moh. (Indonesian Journal of Emerging Trends in Community Empowerment, 2025)
Higher education in Indonesia faces significant challenges in improving students’ ability to write scientific papers. Amid the crucial role of scientific papers as a means of communicating research findings, students of the Distance Learning Program at UIN Siber Syekh Nurjati Cirebon often encounter difficulties in developing this skill due to limited direct interaction and access to academic resources. The community service activity aims to improve scientific writing literacy among students of the Distance Learning Program at UIN Siber Syekh Nurjati Cirebon through training and workshops. This program focuses on two main aspects: (1) enhancing the ability to write systematic scientific papers that adhere to academic standards, and (2) introducing and utilizing digital resources to support writing and academic research. Through a practical approach, students are expected to produce high-quality scientific papers and become more competent in the academic field. The expected outcome of this program is the improvement of the quality of students' scientific papers, as well as the development of more effective research skills, which in turn can support the enhancement of academic and professional achievements among Distance Learning Program students at UIN Siber Syekh Nurjati Cirebon.